Effect of Pink Rock Rose Extract with or Without Ascorbic Acid and Sodium Ascorbate for the Preservation of Ready-to-Eat Frankfurter Type Sausages - Ayça Gedikoğlu; Hale İnci Öztürk; Sencer Buzrul; Münevver Sökmen; Ezgi Aytaç (Turkish Journal of Agriculture: Food Science and Technology)
This study aimed to determine the effect of pink rock rose extract (PRR) with or without ascorbic acid and sodium ascorbate for improving the shelf life of sausages. Analyzed parameters were DPPH radical scavenging capacity of PRR extract; total aerobic count, thiobarbituric acid reactive substance, heme iron, pH, water activity, proximate composition, and color values of MAP packaged sausages for 12 weeks at 4 °C. Treatments: (1) Control (0.02% ascorbic acid and 0.05% sodium ascorbate – AA-SA), (2) electrostatic spray application of PRR extract (2%) – ES-PRR, (3) 0.02% AA and, 0.05% PRR extract, (4) 0.05% SA and 0.02% PRR, (5) 0.07% PRR extract. PRR extract had the half maximal inhibitory concentration (IC50) value of 13.04 ± 0.133 µg/mL. Sausages formulated with 0.07% PRR had the lowest microbial growth rate, followed by AA-PRR formulation. The AA-PRR treatment had the lowest TBARS values for most of the storage. This study reveals that PRR extract can be added as a natural antioxidant in sausages, and it could be used as a replacement or for the reduction of ascorbic acid and sodium ascorbate in sausage formulations.